1992
DOI: 10.1099/00207713-42-3-499
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal DNA Restriction Analysis Reveals Genetic Heterogeneity in Saccharomyces cerevisiae Meyen ex Hansen

Abstract: A ribosomal DNA restriction analysis of 17 strains belonging to the Succhromyces cerevkiue complex revealed two major groups, one of which corresponded to Succharomyces buyunus. Our results generally correlate with previously reported genetic and molecular data and support the conclusion that S. buyunus should be reinstated as a separate taxon.The schemes currently used for classifying yeasts in the genus Saccharomyces are based largely on physiological features, such as fermentation reactions and resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Furthermore, the 900-base sequences from S. pastonanus and S. bayanus were identical, and those from S. cerevisiae and S. paradoxus differed in only five nucleotides. rDNA restriction analysis from PCR-amplified fragments (13,(23)(24)(25) has also been used recently to differentiate between strains belonging to S. cerevisiae, S. bayanus, and S. pastorianus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the 900-base sequences from S. pastonanus and S. bayanus were identical, and those from S. cerevisiae and S. paradoxus differed in only five nucleotides. rDNA restriction analysis from PCR-amplified fragments (13,(23)(24)(25) has also been used recently to differentiate between strains belonging to S. cerevisiae, S. bayanus, and S. pastorianus.…”
Section: Discussionmentioning
confidence: 99%
“…These include DNA fingerprinting (5,(31)(32)(33)(34)42), chromosomal DNA profiles (7,9,14,15,21,27), mitochondrial DNA (mtDNA) restriction analysis (22,48), and rRNA and ribosomal DNA (rDNA) sequencing (18) as well as restriction analysis (13,(23)(24)(25). Until now, only electrophoretic karyotyping, rRNA sequencing and rDNA restriction analysis have proved useful for differentiating Saccharomyces species.…”
mentioning
confidence: 99%
“…However well-separated the ' cerevisiae' and 'bayanus' clusters may be, they consist of very closely related yeasts when the whole genus Saccharomyces is considered (7,11,12,13). Thus, a phylogenetic tree based on the 18s gene sequences of species belonging to Saccharomyces and related genera showed that the genus Saccharomyces is very heterogeneous, whereas the species of the Saccharomyces sensu stricto complex form a natural group quite separated from other Saccharornyces and non-Saccharomyces species examined (7).…”
Section: Discussionmentioning
confidence: 99%
“…Because ribosomal regions evolve in a concerted fashion, they show a low intraspecific polymorphism, and a high interspecific variability (Li, 1997) has been proved very useful for the classification of Saccharomyces species (Huffman et al, 1992;Molina et al, 1992;Valente et al, 1996;Wyder & Puhan, 1997), Kluyveromyces species (Belloch et al, 1998) and, recently, for the identification of a small collection of wine yeast species (Guillamon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%